The Differences in DEQ-5 Results Between DM and Non-DM Patients in the Age of 45-80 Years at Ukrida Hospital - Hidayat, Aji Nur; Lesmana, Michael Indra; Goenawan, Kristian (Universitas Kristen Krida Wacana, 2025)
Dry eye syndrome is a common complaint, especially in the elderly and people with diabetes mellitus (DM). Diabetes can affect the quality and stability of the tear film. Subjective assessment using the Dry Eye Questionnaire-5 (DEQ-5) is often used to screen for dry eye symptoms. Purpose: To determine the differences in DEQ-5 scores between DM and non-DM patients aged 45–80 years at Ukrida Hospital. Method: This study used an observational analytical design with a cross-sectional approach. The sample consisted of 200 respondents divided between DM and non-DM patients. Data collection was carried out by distributing the DEQ-5 questionnaire, and the results were analyzed using the Chi-Square test. Results: A total of 30.5% of respondents experienced dry eye symptoms. There was no significant difference in DEQ-5 scores between DM and non-DM groups (p = 0.746), or in the age subgroups <55 years (p = 0.846) and >56 years (p = 1.000). Conclusion: There was no significant difference in DEQ-5 scores between DM and non-DM patients aged 45–80 years. Other factors such as glycemic control, duration of DM, and use of topical therapy may also affect dry eye symptoms.